Should I want to live to 100? - Pence, Gregory E. (Bioethics, 2019)
Is it virtuous for someone to try to live to 100? Casting aside questions of intergenerational justice and internal obligations in families, what about the basic desire itself? Discussions of longevity and aging in bioethics are skewed to controversial end-of-life decisions, largely avoiding questions of how to age well before such decisions arise. Respected writers such as Atul Gawande, Daniel Callahan, and Ezekiel Emanuel champion accepting a natural life span and not trying to live beyond it. The Stoic Seneca says a desire to live to 100 is foolish because, however long people live, they waste most of their lives, so if they lived a thousand years, they would still waste most of it. Against Seneca and Emanuel, we argue that a functional, not a chronological, view of aging should guide us and that for some seniors, hoping to be centenarians may be neither foolish nor misguided. Using Cicero, we argue that the pleasures of seniors are not necessarily inferior to those of youth and may even surpass them. Finally, we agree with Emanuel that the “symptom burden” of some lives makes living to 100 unpalatable and with Seneca that, given life’s vicissitudes, we should not plan on living to 100, but heeding his wisdom, try to make the most of the time given to us.